PENGARUH PENDAPATAN, PENDIDIKAN, DAN REMITAN TERHADAP PENGELUARAN KONSUMSI PEKERJA MIGRAN NONPERMANEN DI KABUPATEN BADUNG (Studi Kasus pada Dua Kecamatan di Kabupaten Badung) - Sili Antari, SE, Msi, Ni Luh (PIRAMIDA, 2012)
Badung Regency is the one of the primary distination area of migrant inBali Province. It’s caused by the development conducted tend to concentrate tothis region, and it’s reflected by the concentration of some activities as well as thecenter of government, economy and trade, education, health services, and thecenter of tourism.The objectives of this rescarch are to know the different of marginalpropensity to consume (MPC) between nonpermanent migrant workers from Baliand outside Bali; the effect of income, education, and remittances on consumptionspending of nonpermanent migrant workers simultaneously; the effect of income,education, and remittances on consumption spending partially; and to know thedominant variable that influence to consumption spending. In this research wasprimary data from 160 respondents of two villages in Badung Regency thase areJimbaran and Dalung. Technique of data analysis is used simple linearregression, multiple linear regression, clasic assumption test, F-test, t-test andanalysis of dominant variable.Some findings of this research are: that the MPC’s of nonpermanentmigrant workers is still low, as well as the MPC’s of nonpermanent migrantworkers from Bali is 0,248 and 0,133 for nonpermanent migrant workers fromoutside Bali. Simultaneously, the income, education, and remittance variables aresignificantly influential to consumption spending of nonpermanent migrantworkers at level of significant 1 percent. Pertially, the income, education, andremittance variables are also significantly influential to consumption spending ofnonpermanent migrant workers at level of significant 1 percent. The last findingthat income is the most dominant variable have an effect to consumption spendingof nonpermanent migrant workers.In relation with aboved conclusions can be suggested: Firstly, the usingremittances thas sent by nonpermanent migrant workers to its origin in order toproductive activities so thas can push the origin area. Secondly, thenonpermanent migrant workers have to pay attention to the environmentalcondition compatibility in distination area, like to participate in social activitiesand to maintain the cleanlines environment in distination area.
Keywords: nonpermanent migrant workers, marginal propensity to consume, and remittance